ОҚЫТЫЎДА ТӘЛИМ МАЗМУНЫНЫҢ БӨЛИМЛЕРИ БОЙЫНША ӨЗЛЕСТИРИЎ ДӘРЕЖЕЛЕРИН АНЫҚЛАЎ - Ильясова, З.К. (FAN va JAMIYAT, 2017)
The article deals with all possible non-standard test forms of tasks of different levels of complication in the subject Informatics. The teacher can choose the necessary didactic test materials for individual tasks and for test questionnaire of control works during the lessons. Answers to the tasks are given, which let the learners use the material both: for self–control and for increasing levels of creativeness and systematization of knowledge.